El exemplum en la tradición epistolar castellana (Carte Romanze, 2022)
This paper examines the links between the exemplum and epistolary traditions throughout the Middle Ages. Starting from a review of what the artes dictaminis stipulated about the use of proverbs and exempla and as a feature of Ciceronianism, it is observed that throughout the epistolary tradition the short story was a recurrent rhetorical device. It is not necessary to wait until the XVth century - the peak of epistolography - to find this crossover. Therefore, both XIVth and XVth century epistolography are reviewed. The difference between the two periods does not lie in the greater or lesser abundance of this technique, but in the type of narratives that were inserted into the letters. The tradition of Valerius Maximus or the historical story gained ground in the XVth century, while that of the fable was more abundant in the previus period. Far from exhausting the subject, this paper offers some first outlines of a connection worth exploring.
Keywords: Exemplum; Letter; Ars Dictaminis; Cicero